Working at the Seams of Colonial Structures: Alternative Sociotechnical Infrastructures Revealed by Hurricane Maria. (March 2023) - Vasquez, Fatima K. Espinoza
This study explains why and how Puerto Rican activists responded effectively to the crisis in the aftermath of Hurricane Maria in 2017. By relying on a structural approach, this study analyzes the local institutional environment. Using the seamful work framework, it examines activists' practice to reveal activists' relation with their official state infrastructure and their interactions with said infrastructure before and after Maria. Using semi-structured interviews, observations, and publicly available documents, this study shows that activists navigate the state's unequal infrastructure by building their infrastructures, called alternative sociotechnical infrastructures, which consist of a set of heterogeneous assortments of actors, organizations, and technologies to address state-driven inequality and natural disasters. Activists do not work to restore existing state infrastructures, instead, they deploy their expertise in their communities to address many of the challenges brought on by disasters. This study emphasizes a bottom-up approach, highlighting local actors' agency by focusing on the convergence of their knowledge, organizations, and Information and Communication Technologies. Moreover, this research proposes that state-community disconnect is rooted in neoliberal and colonial measures and cautions against considering disasters as opportunities to start anew. Finally, this research proposes new possibilities to plan bottom-up relief efforts that acknowledge the role of civil society and activists.